TROPONIN USE IN EMERGENCY DEPARTMENT SYNCOPE. Issue 12 (23rd November 2015) - Reed, M.J.; O'Neill, A
Abstract : Objectives & Background: There is evidence to suggest that contemporary troponin assays predict serious outcome in syncope, however recent data from newer high sensitive assays show less predictive accuracy. It is still unclear where troponin fits into Emergency Department (ED) syncope decision-making, and also where current practice lies. The aims of this study were: (1) to assess current use of troponin by clinicians in ED syncope patients, and (2) to assess whether a high sensitive troponin assay is better able to predict outcome in ED patients presenting with syncope than a contemporary assayTable 1 . Methods: Single centre retrospective ED cohort study. Eligible patients were identified by way of an electronic patient record keyword search, then individually searched. Patient's contemporary troponin (Abbott Architect troponin I; Abbott Laboratories, Abbott Park, Illinois) and high sensitive troponin assays (Abbott Architect STAT high sensitivity troponin I) were recorded. Both were being measured in our ED during this period, only the contemporary being released to clinicians. Serious outcome at one month and one year was recorded. Results: Between 1st November 2012 and 31st January 2013, there were 27, 878 presentations to the ED. 27, 128 patients were non syncopal, and 497 had an exclusion criteria. 253 patients were enrolled in study. Mean age was 59.0 (SD 24.7). 19 (8%) patients were reported to have chest pain and 36 (14%) patients had ECG changes suggestive of ACS, 5 had both. 100 (40%) patients were admitted to hospital. 15 (6%) patients had a serious outcome at one month and 43 (17%) patients at one year. At one year, 26 (10%) patients had died. Troponin was measured in 43 patients (17%). 29 (67%) had chest pain and/or ECG changes. Troponin was more likely to be measured in a patient with chest pain (p <0.001; Chi-squared 15.86, df=1) or ECG changes (p <0.001; Chi-squared 54.31, df=1). 5 of 43 patients had a raised initial contemporary troponin (≥0.05 ng/ml). 7 of 43 patients had a raised initial sensitive troponin (men ≥34 ng/L, women ≥16 ng/L). ROC analysis is detailed in the table. Conclusion: ED clinicians are more likely to order troponin in syncope patients that present with chest pain or ECG changes, symptoms characteristic of ACS in line with current NICE guidelines. A high sensitivity troponin is able to predict serious outcomes at one month and one year much better that the contemporary troponin assay.